2022
DOI: 10.3233/jad-220019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chronic Paroxetine Treatment in Mitigating Amyloid Pathology and Microgliosis in APPSWE/PS1ΔE9 Transgenic Mice

Abstract: Background: Modulation of serotonergic signaling by treatment with selective serotonin reuptake inhibitors (SSRIs) has been suggested to mitigate amyloid-β (Aβ) pathology in Alzheimer’s disease, in addition to exerting an anti-depressant action. Objective: To investigate the efficacy of chronic treatment with the SSRI paroxetine, in mitigating Aβ pathology and Aβ plaque-induced microgliosis in the hippocampus of 18-month-old APP swe/PS1 ΔE9 mice. Methods: Plaque-bearing APP swe/PS1 ΔE9 and wildtype mice were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In this section, we review other studies and discuss the impact of chronic SSRI treatment on the formation of β-amyloid, considering potential outcomes such as protective effects, no discernible impact, or an increase in plaque load. Consistent with our results, Severino et al and Sivasaravanaparan et al showed that chronic paroxetine therapy, administered at a dosage of 10 mg/kg/day in drinking water, elevated mortality rates in APP/PSEN1 transgenic mice aged 9–18 months ( Severino et al, 2018 ; Sivasaravanaparan et al, 2022 ). Notably, a substantial improvement in survival outcomes was observed when the dosage was reduced to 5 mg/kg/day during the same age range.…”
Section: Discussionsupporting
confidence: 93%
“…In this section, we review other studies and discuss the impact of chronic SSRI treatment on the formation of β-amyloid, considering potential outcomes such as protective effects, no discernible impact, or an increase in plaque load. Consistent with our results, Severino et al and Sivasaravanaparan et al showed that chronic paroxetine therapy, administered at a dosage of 10 mg/kg/day in drinking water, elevated mortality rates in APP/PSEN1 transgenic mice aged 9–18 months ( Severino et al, 2018 ; Sivasaravanaparan et al, 2022 ). Notably, a substantial improvement in survival outcomes was observed when the dosage was reduced to 5 mg/kg/day during the same age range.…”
Section: Discussionsupporting
confidence: 93%
“… Morgese et al (2021) reported that serotonin levels were decreased in Aβ-injected rats which was established as a rat model mimicking the early phase of AD. In another recent experiment ( Sivasaravanaparan et al, 2022 ), nevertheless, chronic treatment with paroxetine—a selective serotonin reuptake inhibitor, failed to mitigate Aβ pathology and microgliosis in APPSWE/PS1ΔE9 mice. In addition, the serotonin transporter ( SLC6A4 ) which regulates the serotonin concentrations and serves as the target of selective serotonin reuptake inhibitors, might be associated with AD risks ( Polito et al, 2011 ; Yamazaki et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, there are issues in both consistency and translational ability of SSRIs' effectiveness in reducing AD pathogenesis and improving cognitive and behavioral deficits. In the APP/PS1 model, studies report no change in Aβ deposition, nor cognitive or behavioral measures (Severino et al, 2018;Sivasaravanaparan et al, 2022;see Mdawar et al, 2020; for a review; refer to Table 9). Although treatments with SSRIs varied in AD rodent models, given that treatment with SSRIs worked in a subsection of AD animal models, both in reducing AD 10.3389/fnagi.…”
Section: -Ht Trends and Treatments In Ad Modelsmentioning
confidence: 99%